Acquired multi‐segment foot kinematics in haemophilic children, adolescents and young adults with or without haemophilic ankle arthropathy. Issue 4 (25th June 2020) - Lobet, Sebastien; Peerlinck, Kathelijne; Hermans, Cedric; Van Damme, An; Staes, Filip; Deschamps, Kevin
Abstract: Introduction and aim: The ankle joint remains vulnerable in children with haemophilia and is the primary joint affected. The purpose of this study was to dynamically characterize the segmental foot and ankle kinematics of male children, adolescents and young adults with or without ankle arthropathy. Methods: The barefoot multi‐segment foot kinematics of 70 ankles from 35 haemophilia subjects between 6 and 20 years old were captured with the Rizzoli Multi‐Segment Foot Model. Joint damage of the tibiotalar and subtalar joints was scored using the IPSG‐MRI score. The feet of patients with or without evidence of ankle arthropathy were compared with those of matched typically developing boys via a nonpaired comparison. The differences between the affected and nonaffected sides of patients with unilateral ankle arthropathy were assessed using a paired comparison. Results: Subjects without arthropathy demonstrated a nonsignificant trend towards a higher frontal plane range of motion (RoM) at the midfoot upon loading response and a lower sagittal plane RoM at the midfoot during midstance. No differences were observed between the affected side group and their matched control group. The affected side of unilaterally affected subjects exhibited a nonsignificant tendency towards a higher frontal plane RoM at the ankle joint upon loading response and terminal stance compared to the healthy side. Conclusion: Most patients maintained physiological rocker function of the ankle and had no (mal)adaptive motion patterns in the more distal joints of the foot. Therefore, established structural lesions may remain subclinical with respect to moderate functional activities like walking.